Experimental study of angle type shear connectors in position L and V embedded in composite slabs with steel decks (Gaceta Técnica, 2022)
This article presents a study of angle-type shear connectors, as a new proposal for a monolithic work of the composite slab system with collaborating sheet, considering that there are currently no regulations that validate its use. The experimental analysis of 14 specimens with angle-type shear connectors positioned in plan at 90º (type L) and 45º (type V), tested with the Push-Out method established by Eurocode 4, is presented. Mechanical properties such as shear strength, ductility, and stiffness as a function of connector position, as well as failure mode. The results showed that the two groups of specimens have similar shear strength and ductility, differentiating between V-type connectors with a stiffness value 42% higher than differentiating between V-type connectors with a stiffness value those obtained in L-type connectors. The typical failure mode is due to premature cracking, of the concrete in the cross section of the slab. The results obtained for shear capacity are compared with some empirical expressions of international regulations and previous studies of similar connectors
Keywords: shear connector; angle type connector; push-out test; collaborating sheet